Cyanobacteria phylogenetic studies reveal evidence for polyphyletic genera from thermal and freshwater habitats - Cordeiro, R. (2020)
Cyanobacteria are among the most diverse morphological microorganisms that inhabit a great variety of habitats. Their presence in the Azores, a volcanic archipelago of nine islands in the middle of the North Atlantic Ocean, has already been reported. However, due to the high diversity of cyanobacteria habitats, their biodiversity is still understudied, mainly in extreme environments. To address this, a total of 156 cyanobacteria strains from Azores lakes, streams, thermal and terrestrial habitats were isolated. Identification was made based on a polyphasic approach using classical taxonomy (morphological characteristics and environmental data) and phylogeny among 81 strains assessed by maximum likelihood and Bayesian analysis of 16S rDNA partial sequences. The 156 isolates showed a high genera diversity (38) belonging to the orders Chroococcales, Nostocales, Oscillatoriales, and Synechococcales. Eleven new genera for the Azores habitats are here reported, reinforcing that cyanobacteria biodiversity in these islands is still much understudied. Phylogenetic analysis showed 14 clusters associated with these cyanobacteria orders, with evidence for six new genera and valuable information towards Microchaete/Coleospermum taxonomic revision that better reflects species environmental distribution. These results emphasize the need for cyanobacteria taxonomy revisions, through polyphasic studies, mainly in Synechococcales order and in the Microchaete/Coleospermum, Nostoc, and Anabaena genera.